Perfomance Appraisal of SEZ in India - Garg, Anju (Journal of Commerce and Trade, 2017)
The creation of SEZ and its contribution in the development of economy of the country is a burning topic which is directly or indirectly related to the social, psychological and economic aspects of the country. In the present paper “Performance Appraisal of SEZ in India”, an attempt is made to critical examine the elements of SEZ. The SEZ policy continues to be relevant from a Make in India perspective but several policy initiatives are necessary to get those going. Manufacturers should be allowed to sell goods in the domestic market but duty should be imposed on individual parts imported and not on the entire product, which would make it unviable. The present study “Performance Appraisal of SEZ in India” is the need of the hour as high priority and aspirant scheme of “Make in India” is executed by PM Modi. SEZ has been assumed as 'engine of growth'. But, it could not perform as thought upon earlier.